2003
DOI: 10.1002/mpo.10285
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell tumours of the central nervous system in children—controversies in radiotherapy

Abstract: The excellent outcome in children with pure germinoma of the CNS and the long-term morbidity associated with standard therapy justifies attempts to limit both the total radiation dose and field sizes, with or without the addition of chemotherapy. The poorer outcome associated with non-germinoma GCT justifies a more aggressive approach in children, combining chemotherapy, surgery and virgule, or radiation therapy, based on known prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
0
17
0
1
Order By: Relevance
“…There is good evidence in the literature describing the progressive linear decline in IQ points among patients receiving whole brain and craniospinal irradiation, ranging from 2 to 5 points per year after completion of radiotherapy . In recent years, significant effort has been focused on therapeutic strategies that limit cranial irradiation, especially in localized germinomas …”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence in the literature describing the progressive linear decline in IQ points among patients receiving whole brain and craniospinal irradiation, ranging from 2 to 5 points per year after completion of radiotherapy . In recent years, significant effort has been focused on therapeutic strategies that limit cranial irradiation, especially in localized germinomas …”
Section: Discussionmentioning
confidence: 99%
“…Pure germinomas are extremely radiosensitive and are successfully cured in over 90% of cases by irradiation alone . Recent studies, however, have demonstrated the utility of using chemotherapy in conjunction with lower doses and limited fields of irradiation with equally successful overall and event‐free survival …”
Section: Discussionmentioning
confidence: 99%
“…Patients with MMGCT have an overall poorer prognosis than those with pure germinomas as MMGCT are not particularly radiosensitive. In studies where these patients were treated with irradiation alone, the overall 5‐year survival was only between 20 and 40% . The best outcomes result from treatment with chemotherapy and targeted irradiation in combination, leading to a 5‐year survival between 50 and 70% …”
Section: Discussionmentioning
confidence: 99%
“…With combination cisplatin chemotherapy, 5-year survival rates are now 67-74% [9,13]. A therapeutic impact of radiotherapy has not yet been established [14], and both indications and extent of the surgery are still unclear [15]. Some studies suggest a therapeutic benefit from tumor debulking [16,17,18], whereas other reports emphasize that malignant GCTs should be treated with radiation therapy and chemotherapy without surgery [19,20].…”
Section: Discussionmentioning
confidence: 99%